Contextualization of Digital literacy-Based Gender Fiqh Education as an Effort to Prevent Students Sexual Violence in Public Universities - Chanifah, Nur; Kusrin, Zuliza Mohd; Habibillah, Putri Ghoida’ (Nadwa: Jurnal Pendidikan Islam, 2024)
This qualitative study is a concrete effort to reduce sexual violence in public universities based on digital literacy with a campaign pattern. Based on cases that continue to increase every year, this study targets students at Brawijaya University and Malang State University who are positioned as the main data. This data is tracked using survey and documentation techniques which are then processed systematically with secondary data in the form of related articles and books. In general, the study focuses on the issue of how the design of gender jurisprudence can be conveyed effectively to students. The results of this study are a special campaign account on Instagram social media called @gendercampaign. This account produces sexual violence prevention content based on gender jurisprudence. An important strategy in this campaign is the maximum use of algorithms, design creativity, content design and Instagram features.